Managing uncertainty and responding to difficult emotions: Cancer patients' perspectives on clinician response during the COVID-19 pandemic. Issue 7 (July 2022) - Street, Richard L.; Treiman, Katherine; Wu, Qiwei; Kranzler, Elissa C.; Moultrie, Rebecca; Mack, Nicole; Garcia, Reese
Abstract: Objective: Patients undergoing cancer treatment during the COVID-19 pandemic have experienced stress and uncertainty with respect to disruptions in cancer care and COVID-19 related risks. We examined whether clinicians' responsiveness to patients' uncertainty and difficult emotions were associated with better health and well-being. Methods: Patients were recruited from cancer support communities and a market research firm. Respondents assessed clinicians communication that addressed uncertainty and difficult emotions. Health status measures included mental and physical health, coping during the pandemic, and psychological distress. Results: 317 respondents participated in the study. Patients' perceptions of their clinicians responsiveness to patient uncertainty and negative emotions were associated with better mental health, physical health, coping, and less psychological distress (all p -values <0.001). Respondents with greater self-efficacy and social support also reported better health. Conclusion: Even when controlling for patients' personal and health-related characteristics, clinicians' communication addressing patients' uncertainty and difficult emotions predicted better health, better coping, and less psychological distress. Access to social support and self-efficacy also were associated with better health status. Practice implications: Clinicians' communication focused on helping with uncertainty and difficult emotions is important to cancer patients, especially during the pandemic. Clinicians should also direct patients to resources for social support and patient empowerment. Highlights: The COVID-19 pandemic added considerable uncertainty and emotional distress for cancer patients. Clinicians' communication that that was responsive to patients' uncertainty and difficult emotions was associated with better self-reported health outcomes. Cancer patients who reported less positive communication experiences with clinicians also reported lower self-efficacy and less social support. Clinicians need skills to enhance their "webside" manner to insure more patient-centered communication experiences for cancer patients.